Study on the impact of the COVID-19 pandemic on the rates of violence against women in the State of São Paulo - Charadias, Samuel Alves (2023)
There is an intercurrence in society and with that there was a need to carry out a study about this topic related to the same period of pandemic. The objective of this article is to carry out a study of the data released to allow an analysis of the rates of violence against women considering the period from 2018 to August 2022, as well as to present a study of the impact caused by the COVID-19 pandemic on the rates of violence against women in the State of São Paulo during and after this period. The methodology used is a bibliographic and descriptive research, where articles published in Brazilian journals available in the Google Scholar database were examined. For the process of analyzing these data, a quantitative analysis was carried out using the Python programming language for manipulation and analysis, in a way that allowed the creation of graphs. With the results obtained, it was possible to identify that there was no significant increase in the rate of violence against women in the state of São Paulo.